Trait‐mediated responses to aridity and experimental drought by springtail communities across Europe. (25th March 2022) - Ferrín, Miquel; Márquez, Laura; Petersen, Henning; Salmon, Sandrine; Ponge, Jean‐François; Arnedo, Miquel; Emmett, Bridget; Beier, Claus; Schmidt, Inger K.; Tietema, Albert; de Angelis, Paolo; Liberati, Dario; et al.
Abstract: The capacity to forecast the effects of climate change on biodiversity largely relies on identifying traits capturing mechanistic relationships with the environment through standardized field experiments distributed across relevant spatial scales. The effects of short‐term experimental manipulations on local communities may overlap with regional climate gradients that have been operating during longer time periods. However, to the best of our knowledge, there are no studies simultaneously assessing such long‐term macroecological drivers with local climate manipulations. We analysed this issue with springtails (Class Collembola), one of the dominant soil fauna groups, in a standardized climate manipulation experiment conducted across six European countries encompassing broad climate gradients. We combined community data (near 20K specimens classified into 102 species) with 22 eco‐morphological traits and reconstructed their phylogenetic relationships to track the evolution of adaptations to live at different soil depths, which is key to cope with desiccation. We then applied joint species distribution models to investigate the combined effect of the regional aridity gradient with the local experimental treatment (drought and warming) over the assembly of springtail communities and tested for significant trait–environment relationships mediating their community‐level responses. Our results show (1) a convergent evolution in all three major collembolan lineages of species adapted to inhabit at different soil strata; (2) a clear signature of aridity selecting traits of more epigeic species at a biogeographical scale and (3) the association of short‐term experimental drought with traits related to more euedaphic life‐forms. The hemiedaphic condition would be the plesiomorphic state for Collembola while the adaptations for an epigeic life would have been secondarily gained. Epigeic springtails are not only more resistant to drought, but also have a higher dispersal capacity that allows them to seek more favourable micro‐habitats after experiencing drier conditions. The observed relative edaphization of the springtail communities after short‐term experimental drought may thus be a transient community response. The disparity between macroecological trends and fast community‐level responses after climate manipulations highlights the need of simultaneously assessing long‐term and short‐term drivers at broad spatial scales to adequately interpret trait–environment relationships and better forecast biodiversity responses to climate change. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: La capacidad de predecir los efectos negativos del cambio climático sobre la biodiversidad depende en gran medida de identificar aquellos atributos que capturan relaciones mecánicas con el ambiente mediante experimentos manipulativos de campo distribuidos a escalas espaciales relevantes. No obstante, los efectos de las manipulaciones experimentales a corto plazo sobre las comunidades locales pueden solaparse con los gradientes climáticos regionales que han operado durante periodos de tiempo más prolongados. No obstante, de acuerdo a nuestro conocimiento, no hay estudios que hayan evaluado simultáneamente factores macroecológicos a largo plazo junto con manipulaciones climáticas a corto plazo a escalas espaciales relevantes. Analizamos este asunto usando como ejemplo a los colémbolos (Clase Collembola), un importante grupo de la fauna del suelo, mediante un experimento de campo de manipulación climática estandarizado y llevado a cabo en 6 países europeos abarcando así amplios gradientes de temperatura y precipitación. Combinamos datos de comunidades de colémbolos (cerca de 20 mil especímenes clasificados en 102 especies) con 22 atributos eco‐morfológicos y reconstruimos sus relaciones filogenéticas para rastrear la evolución de las adaptaciones para vivir a distintas profundidades del suelo, lo cual es clave para lidiar con la sequedad. Aplicamos entonces modelos de distribución conjunta de especies para investigar el efecto combinado del gradiente regional de aridez con el tratamiento experimental local (sequía y calentamiento) sobre el ensamblado de las comunidades de colémbolos, y además, testamos la existencia de relaciones atributo‐ambiente significativas mediando las respuestas de las comunidades de colémbolos a las manipulaciones climáticas. Nuestros resultados muestran: (1) una evolución convergente en los tres linajes principales de colémbolos de especies adaptadas a habitar en distintos estratos del suelo. (2) una clara signatura de la aridez seleccionando atributos de especies más epigeas a escala biogeográfica, y (3) la asociación de la sequía experimental a corto plazo con atributos relacionados con formas de vida más eu‐edáficas. La condición hemiedáfica seria el estado plesiomórfico de Collembola mientras que las adaptaciones a una vida completamente epigea habrían sido desarrolladas secundariamente y de manera repetida en distintos linajes. Los colémbolos epigeos son más resistentes a la sequía pero también presentan una capacidad de dispersión mayor lo cual les permite buscar activamente micro‐hábitats más favorables tras experimentar condiciones ambientales adversas. La relativa edafización de las comunidades de colémbolos observada tras la sequía experimental a corto plazo seria por lo tanto una respuesta transitoria de la comunidad. La disparidad entre las tendencias macroecológicas y las rápidas respuestas a nivel de comunidad tras las manipulaciones climáticas ponen de manifiesto la necesidad de evaluar simultáneamente factores de cambio ambiental operando a corto y a largo plazo, y a escalas espaciales amplias, para poder interpretar adecuadamente las relaciones entre atributos y ambiente y así poder predecir mejor las respuestas de la biodiversidad al cambio climático.